2019
DOI: 10.1097/paf.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Depressions of Dermestes maculatus (Coleoptera: Dermestidae) on Bones Could be Pupation Chambers

Abstract: Dermestes maculatus DeGeer beetles feed and can leave marks on bones. This species is of medical, veterinary, and forensic importance. The aim of this work was to determine if the depressions produced on bones by these beetles could be product of pupation. We studied under controlled conditions the behavior of D. maculatus larvae maintained at 24°C ± 3°C, 52.7% average relative humidity, and a 12:12-hour light/dark cycle and fed on pig carcasses. Observations were made, and photographs were taken. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
0
8
0
13
Order By: Relevance
“…Our analysis points to the action of insects on different bone stages: two avian bones distinctly display evidence of light weathering over the cortical surface except on traces. Moreover, Zanetti and co-authors [43] found that dermestids consumed and marked burned tissues. The selection of bones at different diagenetic stages could be related to the consumption of various trace elements (calcium, phosphorus and nitrogen), proteins and lipids [6].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our analysis points to the action of insects on different bone stages: two avian bones distinctly display evidence of light weathering over the cortical surface except on traces. Moreover, Zanetti and co-authors [43] found that dermestids consumed and marked burned tissues. The selection of bones at different diagenetic stages could be related to the consumption of various trace elements (calcium, phosphorus and nitrogen), proteins and lipids [6].…”
Section: Discussionmentioning
confidence: 97%
“…Holden et al [35] registered bores that ranged between 2.5 and 3.5 mm in diameter after their live experiments with dermestids. Also, Zanetti et al [42,43] documented that D. maculatus feeds on bone and in the process generates diverse traces (e.g., spherical or ovoid depressions for refuge and pupation). They observed that, in some cases, the largest marks measure more than one centimeter.…”
Section: Discussionmentioning
confidence: 99%
“…The first fossil record of dermestid beetles comes from the Late Cretaceous (Parkinson 2013). According to actualistic experiments performed by Zanetti et al (2019), the dermestid beetles could produce pupation chambers on bones. Besides, it is known that dermestid larvae feed on carrion and perforate various durable substrates (wood and stone) during pupation (Hefti et al 1980;Kirkland & Bader 2010;Holden et al 2013;Zanetti et al 2014Zanetti et al , 2019.…”
Section: Identity Of the Potential Producer Of The Trace Fossils At B...mentioning
confidence: 99%
“…According to actualistic experiments performed by Zanetti et al (2019), the dermestid beetles could produce pupation chambers on bones. Besides, it is known that dermestid larvae feed on carrion and perforate various durable substrates (wood and stone) during pupation (Hefti et al 1980;Kirkland & Bader 2010;Holden et al 2013;Zanetti et al 2014Zanetti et al , 2019. To infest a corpse, these insects need a carcase of a dead animal with dry skin and dried soft tissues (muscles, tendons, and cartilage), in other words to be in a dry stage of decomposition.…”
Section: Identity Of the Potential Producer Of The Trace Fossils At B...mentioning
confidence: 99%
“…(Harold, 1872) According to frequency in studies reviewed and forensic importance ratios presented here, Dermestes and Necrobia genera are the most relevant beetles of forensic importance in Peru and elsewhere. Recently, it has been shown that the species of these genera leave significant traces on carcasses, marks on epithelial and connective tissues caused by feeding activity of Necrobia rufipes (DeGeer, 1775) (Zanetti et al 2015b), and bone depressions caused by feeding and pupation of Dermestes maculatus DeGeer, 1774 (Zanetti et al 2018). The identification of these species is relatively simple, with valid keys for wide geographic areas, since the species of these genera are cosmopolitan and, in many cases, also pests of stored products (Midgley et al 2010).…”
Section: Potential Speciesmentioning
confidence: 99%